PENERAPAN MODEL KONSTRUKTIVIS-METAKOGNITIF PADA MATERI SISTEM KOORDINASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI MIA 1 SMA NEGERI 6 SURAKARTA TAHUN PELAJARAN 2015/2016 - Yunita Nur Anggraeni; Baskoro Adi Prayitno; Joko Ariyanto (BIO-PEDAGOGI, 2016)
This study aims to improving critical thinking skills of student of class XI MIA 1 SMA Negeri 6 Surakarta in the academic year 2015/2016 through the implementation of Constructivist-Metacogitive model. This research considered as Classroom Action Research that performed whitin 2 cycles and consist of 4 steps namely planning, action, observation, and reflection. The research procedure refers to Kemmis-Mc.Taggart spiral technique. Data are obtained by questionnaire, essay test, interview, and documentation. Data analysis using qualitative descriptive technique. The main data regarding students' critical thinking skills covering several aspects, namely the interpretation, analysis, evaluation, inference, explanation and self-regulation was measured using a test arranged by the researcher. Data analysis using descriptive analysis technique. Data validation using triangulation techniques. The average yield of pre-cycle critical thinking skills is 33.71% (low), then increased to 47.6% (average) at the first cycle, and increased to 75.76% (high) at the second cycle. The student’s critical thingking skill improvement have reached the reseach target (≥20%), Thus, application of constructivist-metacognitive models can improve students' critical thinking skills. The results showed that the application of Constructivist Model-metacognitive improving critical thinking skills of the students of class XI MIA 1 SMA Negeri 6 Surakarta.Keywords: Constructivis-metacognitive models, Critical Thinking Skills, Coordination System.